Good Habits Program Management Strengthens Student Discipline and Social Character: Program Pengelolaan Kebiasaan Baik Meningkatkan Disiplin dan Karakter Sosial Siswa - Rifatul Fitriya Dewiningsih; Moch.Bahak Udin By Arifin (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Character education in elementary schools plays a fundamental role in shaping disciplined and socially responsible learners. Specific Background: Students at the elementary level often demonstrate tardiness, rule violations, and limited social awareness, indicating weaknesses in discipline and social character development. Knowledge Gap: Although various character-building activities have been implemented in schools, limited studies examine how systematic program management contributes to strengthening both discipline and social character simultaneously. Aims: This study aims to analyze the management of the Good Habits program in fostering student discipline and social character at SDS Muhammadiyah Ngoro. Results: Using a qualitative descriptive case study with observation, structured interviews, and documentation, the findings reveal that structured planning, implementation, and evaluation of activities such as morning greetings with 5S, Dhuha prayer, Healthy Friday, Charity Friday, Quran recitation monitoring, and congregational worship supervision are associated with improved punctuality, rule compliance, responsibility, empathy, and respectful interaction among students. Novelty: The study highlights an integrated school management approach that systematically organizes habitual character-based activities within a collaborative framework involving teachers and parents. Implications: These findings provide practical insights for elementary school management in designing structured character programs to cultivate disciplined behavior and strong social values among learners. Keywords: Good Habits Program, Discipline, Social Character, Elementary School Management, Character Education Key Findings Highlights: Structured school planning and evaluation procedures support consistent character-building routines. Regular religious and social activities are associated with improved punctuality and responsibility. Collaborative involvement of teachers and parents sustains positive behavioral development.